IMPLEMENTASI ICE BREAKING DALAM PEMBELAJARAN SOSIOLOGI SEBAGAI UPAYA PENGEMBANGAN KARAKTER SISWA FASE F SMAN 1 BASA AMPEK BALAI TAPAN - Herlisa Nola Putri; Sarbaitinil; Erningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the crucial issue of low character among students. So in addressing this, the need for student character education. Along with the development of the times at this time, many students appear to have low character, coming to school late, sleeping during class hours and others. This study aims to determine how the process of applying ice breaking as an effort to develop student character through sociology learning, what characters develop in students through ice breaking. This research uses B.F Skinner's theory with a descriptive qualitative approach, this type of research is field research. The technique of selecting informants in this study is purposive sampling technique. Data collection methods in this research are participant observation, semi-structured interviews and document studies. The data analysis used in this research is the Miles and Huberman (1984) model. Based on the results of the study, it can be seen that the current condition of student character is very clearly declining, it can be seen that students lack respect for their friends, cannot solve problems peacefully, lack of active participation in class, sleep during the learning process. Ice breaking activities can develop students' character values, namely tolerance, hard work, creativity, independence, curiosity, respect for achievement, friendship/communication, peace love and responsibility.